Congenital common bile duct cyst - Fadi Rayya; Maram Baloulli; Yusra Alshaikha (Elsevier, 2019)
Congenital bile duct cyst is a cystic dilation of extrahepatic duct, intrahepatic duct, or both. It is a rare condition that affects different ages, especially the neonates. In this paper, we report a case of a 13-year-old girl who was admitted with a chronic right hypochondriac pain without any other clinical findings. Further investigations showed a common bile duct cyst (Todani type IA). The treatment consisted of cholecystectomy and complete surgical excision of the cyst with Roux-en-Y hepaticojejunostomy HJ. The patient did not suffer any complications during or after surgery. She was discharged one day after the surgery, and she is still under close medical supervision so far. Keywords: Congenital common bile duct cyst, Excision, Hepaticojejunostomy, Syria